Stress-strain state of hip joint in children with aseptic femoral head necrosis (the first message) - Korolkov, Oleksandr; Katsalap, Yelyzaveta; Mykhaylo, Mykhaylo; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Aseptic femoral head necrosis in children has a polyethiological structure and leads to the formation of various deformities or the entire proximal femur. Consequences of this may be the early development of hip joint arthritis. Objective: to study the stress-strain state of the hip joint components in cases of femoral head defects of 25 % of its size with different localization due to aseptic femoral head necrosis in children. Methods: a simplified finite element model of the childʼs hip joint was constructed and mathematical studies of the stress-strain state were performed in the normal joint and modeling of the femoral head defect with a 25 % of its volume. The defect was located in the lower and middle parts of the femoral head, in the zone of its loading and at the boundary of the upper edge of the acetabulum. The study of the stress-strain state model was made under the influence of a vertical load of 270 N, and also simulated the effect of the gluteus medius (450 N) and gluteus minimus (200 N) muscles. Results: Normally the main loading transfers through the cortical layer of the femur, the tensions in the cancellous bone are insignificant. The most stressed zone is the femoral neck, especially in the upper part, in the area of its transition to the head under the growth zone. In the case of a defect in the medial and upper parts of the femoral head, slight changes of the stress-strain state were found, and at the border of the upper edge of the acetabulum and in the growth zone — were pronounced. The maximum stress level reached 22.0 MPa, which is 2.5 times higher than the norm. Conclusions: as for to stress distribution in hip joint models, the most unfavorable position is the location of the defect in size 25 % of the femoral head volume at the border of the upper edge of the acetabulum and in the upper part of the femoral head, in the zone of its main load. It is with this option that the highest level of stress is observed on all the sites of the femur.